Algoritmos de remoção para a estrutura de indexação Onion-tree - Marrach, Debora Gonçalves Rodrigues (2013)
The Onion-tree is an efficient metric access method based on main memory for similarity search. The Onion-tree has already provided algorithms for insertion and processing of similarity queries (range query and k-nearest neighbors query). However, in the literature no algorithm has been proposed for removing elements in Onion-tree. For this index be incorporated into a database management system, it is necessary the proposal and implementation of at least one algorithm of deletion. This master's research focused primarily on the implementation and performance evaluation of the algorithms proposed for logical deletion in (CARÉLO et al., 2011). The proposal presented in (CARÉLO et al., 2011) led to the implementation of three algorithms, called LogicalDelete, ReplaceReducing and ReplaceGrowing. The first algorithm applies the logic deletion, while the other two algorithms are specializations adding special treatment for the deletion of elements in internal nodes with children exclusively leaf. The ReplaceReducing algorithm allows the reduction of the radius of the node that contains de deleted element. On the other hand, the ReplaceGrowing algorithm allows increasing this radius. In addition, algorithms have been proposed and evaluated for physical deletion that can be applied at any level of the Onion-tree. The algorithm ReorgAll rearranges all the elements in the hierarchy of the node that contains de deleted element, by physically removing the elements and reinserting them using the insertion algorithm, and algorithm PromoteNode, which extends the algorithm ReorgAll, promotes, when exists conditions for such operation, other node to replace the one that contains the deleted element. Experimental evaluation of the algorithms LogicalDelete, ReplaceReducing and ReplaceGrowing showed that the algorithm LogicalDelete is more cost effective than the algorithms ReplaceReducing and ReplaceGrowing in query processing after the deletion of elements. Experimental evaluation of physical removal algorithms showed that the promotion of a node to replace the removed node has advantages over the simple reorganization of the hierarchy of the node that contains the deleted element. Besides presenting lower cost of deletion of elements, the algorithm PromoteNode also outperformed the algorithm ReorgAll in query processing after removing elements. When compared with the logic deletion algorithm, for a large amount of deletion operations, the algorithms ReorgAll and PromoteNode produced performance gain of 21.6% in range query processing. However, in the same comparison, these algorithms have a much higher cost of deletion.